New Key Exchange Protocol Based on Mandelbrot and Julia Fractal Sets. - Alia, Mohammad Ahmad; Samsudin, Azman (Dr. Sang H. Lee, 2007)
In this paper, we propose a new cryptographic key exchange protocol based on Mandelbrot and Julia Fractal sets. The Fractal based key exchange protocol is possible because of the intrinsic connection between the Mandelbrot and Julia Fractal sets. In the proposed protocol, Mandelbrot Fractal function takes the chosen private key as the input parameter and generates the corresponding public key.